Indikator Kinerja Utama Program Bantuan Sosial Pangan di Indonesia: Analisis Faktor Konfirmatori - Istiana Hermawati, Ikhsanudin, Safa’at Ariful Hudha, Risnandar (Program Studi Pembangunan Masyarakat Desa (D3), 2022)
Poverty and limited access to welfare make it difficult for most poor people in Indonesia to meet their basic needs, especially food needs. One of many efforts made by government, especially in the Ministry of Social Affairs to overcome the problem of poverty and improve people's food security, is through a social welfare program namely Non-Cash Food Assistance (BPNT). This study aims at finding the empirical evidence for the measurement of the key performance indicators of the BPNT in Indonesia. This study is a quantitative approach involving 1530 subject respondents, consisting of beneficiary families, program assistants, and stakeholders from 34 cities/districts. Samples were determined by a multistage sampling in randomized. A questionnaire was used to collecting the data. Collected data were analyzed confirmatory factor analysis using Lisrel 8.50. Fitness of the measurement construct is determined based on nine criteria of fitness. The results prove that the construct for measuring the performance of the BPNT in Indonesia is formed by seven indicators, namely right target, right quantity, right price, right administration, right time, right quality, and right benefits (abbreviated as 7R). The test results prove, that all the criteria for the fit of the model are met. This means the performance of BPNT program could be measured using these seven aspects so that it can be known how well the process of the food welfare program in the field is. This evidence of measurement construct is also a form of instrument validation which can then be recommended for use in future BPNT program evaluation activities